2010
DOI: 10.1346/ccmn.2010.0580212
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Temperature, pH, and Iron/Clay and Liquid/Clay Ratios on Experimental Conversion of Dioctahedral Smectite to Berthierine, Chlorite, Vermiculite, or Saponite

Abstract: In deep geological repositories for high-level nuclear wastes, interactions between steel canisters and clay-rich materials may lead to mineralogical transformations with a loss of the confining properties of the clays. Experiments simulating the conversion of smectite to Fe-rich clay phases in contact with Fe metal have been carried out to evaluate such a possibility by taking into account the effects of a series of critical parameters, including temperature, pH, and Fe/clay (Fe/C) and liquid/clay (L/C) ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(31 citation statements)
references
References 33 publications
0
30
1
Order By: Relevance
“…Recent reviews of experimental work emphasizing mineral paragenesis and clay mineral alteration show a rather convergent set of observations (Wersin et al, 2008;King, 2009;Mosser-Ruck et al, 2010;Savage, 2012). Mineral characterization from iron-clay mineral interaction systems in a wide range of conditions show that magnetite (sometimes associated with maghemite g-Fe 2 O 3 ) is commonly observed adhering to the iron surface in most of the occurrences (experiments and archaeological artifacts) either as (1) a submicrometric internal corrosion layer (Lantenois et al, 2005;Charpentier et al, 2006;Smart et al, 2006;Carlson et al, 2007;Martin et al, 2008;Schlegel et al, 2008Schlegel et al, , 2010De Combarieu et al, 2011;Schlegel et al, 2014) or (2) a thinner, sometimes discontinuous, layer (w10e100 nm) as observed using scanning transmission X-ray microscopy (Michelin et al, 2012).…”
Section: Steel Corrosion In Claymentioning
confidence: 95%
See 1 more Smart Citation
“…Recent reviews of experimental work emphasizing mineral paragenesis and clay mineral alteration show a rather convergent set of observations (Wersin et al, 2008;King, 2009;Mosser-Ruck et al, 2010;Savage, 2012). Mineral characterization from iron-clay mineral interaction systems in a wide range of conditions show that magnetite (sometimes associated with maghemite g-Fe 2 O 3 ) is commonly observed adhering to the iron surface in most of the occurrences (experiments and archaeological artifacts) either as (1) a submicrometric internal corrosion layer (Lantenois et al, 2005;Charpentier et al, 2006;Smart et al, 2006;Carlson et al, 2007;Martin et al, 2008;Schlegel et al, 2008Schlegel et al, , 2010De Combarieu et al, 2011;Schlegel et al, 2014) or (2) a thinner, sometimes discontinuous, layer (w10e100 nm) as observed using scanning transmission X-ray microscopy (Michelin et al, 2012).…”
Section: Steel Corrosion In Claymentioning
confidence: 95%
“…This pH perturbation is responsible for the presence of a transformed clay mineral layer showing systematic dissolution of primary clay minerals: in experiments with clay-rocks, illite, and I-Sm (Jodin-Caumon et al, 2012) tend to dissolve preferentially along with the occasional destabilization of quartz and dolomite (Bourdelle et al, 2014). In experiments involving bentonite, the primary Sm is strongly altered (De Combarieu, 2007;Perronnet et al, 2007;Mosser-Ruck et al, 2010). Along with the influx of iron, the system evolves with the precipitation of either Fe-serpentine (Lantenois et al, 2005;Perronnet et al, 2008;Schlegel et al, 2008Schlegel et al, , 2010De Combarieu et al, 2011;Jodin-Caumon et al, 2012;Bourdelle et al, 2014) or iron-rich Sm (Guilllaume et al, 2004;Charpentier et al, 2006;Wilson et al, 2006a).…”
Section: Steel Corrosion In Claymentioning
confidence: 99%
“…The experiments by Charpentier et al (2006) were conducted under more strongly alkaline conditions than other experiments and resulted in the formation of significant amounts of iron-rich vermiculite under higher temperature conditions (300ºC). In addition to temperature, the influence of a number of other factors (iron:clay ratio, starting smectite composition) have been considered as having an influence on the identity of alteration products observed in experiments (Mosser-Ruck et al, 2010) and there has been discussion as to the mechanisms by which alteration occurs (Lantenois et al, 2005;Perronnet et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Velde et al 1986;Bruce et al 1987;Freed & Peacor 1989;Velde & Vasseur 1992;Lanson et al 2009;Mosser-Ruck et al 2010). A review of thermal stability of bentonite is given by Meunier et al (1998).…”
mentioning
confidence: 99%
“…There is no single thermal activation energy for such reactions to occur, as these processes are highly dependent on the geochemistry of the system (e.g. Mosser-Ruck et al 2010). However, recent work by Pusch et al (2010) suggests that early-onset hydraulic degradation (i.e.…”
mentioning
confidence: 99%